Enforcements Innovation of Shophouse Building to Sustain Resistance on High Risk Earthquakes Area - Cahyono, Heru Setiyo; Mulyono, Julius; Mochammad Hendy, Wicaksono (Widya Teknik, 2025)
Indonesia is one of the most seismically active regions in the world, with many of its cities located in high-risk earthquake zones. Malang, situated in East Java, lies in one of these critical seismic regions, making earthquake-resistant design and construction essential to safeguarding lives and minimizing property damage. This study explores an innovative approach to reinforcing shophouses in Malang, focusing on the use of shear reinforcement in the plastic hinge areas to improve seismic resistance. In particular, the research examines the application of high-strength shear reinforcement strategies as specified by the SNI 1727 : 2020 and SNI 2847 : 2019 standards. The SNI 1727 : 2020, and SNI 2847 : 2019 that all standards provides guidelines for structural requirements, both integral to ensuring safety and durability under seismic loads. This research will contribute to the development of safer construction methods for buildings in high-risk earthquake zones. and aims to support architects, engineers, and builders in meeting current seismic regulations while optimizing structural integrity and cost-efficiency. Obtained the value for 2nd floor plate reinforcements are left supporting reinforcements : ø 8 – 180, field reinforcements : ø 8 – 180, right supporting reinforcements : ø 8 – 250, shear reinforcements : ø 6 – 250, left supporting reinforcements : ø 8 – 180. Obtained the value for beam width (bw) = 200 mm, beam height (h) = 400 mm, concrete blanket (cb) = 40 mm, diameter of main reinforcement = 16 mm, diameter of stirrup reinforcement = 10 mm. Obtained the value for reinforcement installed : main reinforcement 6 ø - 12 mm and reinforcement installed : ø 10 - 150 mm stirrups. Built foot plate dimensions is 0.4 m X 0.3 m and X and Y direction bending reinforcement used reinforcement are D 13 – 200. Used X an Y direction shrinkage reinforcement spacing are 200 mm.